New campus-Psychology and Human Services building-0001
Thousands of students obtain to large part of their training in the Education-Psychology Building, which has been described as among the most modern classroom structures in the nation. It houses 29 classrooms and special facilities fot the education division and the psychology, foreign language, and mathematics departments. The ""Ed-Psych"" Center is the focal structure of the quadrangle centered on the new Fresno State College campus.